Designing Distributed Recommender Systems using Map Reduce Paradigm -A Study - Chakraborty, P.S (International Journal of Computer Sciences and Engineering, 2025)
Nowadays Recommender Systems play an important role in E-Commerce domain. It helps customers to buy the right product or service by generating recommendations. In this paper, a detailed survey has been made regarding the works proposed by different researchers for designing recommender systems in distributed environment. A general framework for designing user-based and item-based recommender systems using map-reduce paradigm has been provide thereafter